Spontaneous Type 2 Diabetic Rodent Models - Yang-wei Wang; Guang-dong Sun; Jing Sun; Shu-jun Liu; Ji Wang; Xiao-hong Xu; Li-ning Miao (Journal of Diabetes Research)
Diabetes mellitus, especially type 2 diabetes (T2DM), is one of the most common chronic diseases and continues to increase in numbers with large proportion of health care budget being used. Many animal models have been established in order to investigate the mechanisms and pathophysiologic progress of T2DM and find effective treatments for its complications. On the basis of their strains, features, advantages, and disadvantages, various types of animal models of T2DM can be divided into spontaneously diabetic models, artificially induced diabetic models, and transgenic/knockout diabetic models. Among these models, the spontaneous rodent models are used more frequently because many of them can closely describe the characteristic features of T2DM, especially obesity and insulin resistance. In this paper, we aim to investigate the current available spontaneous rodent models for T2DM with regard to their characteristic features, advantages, and disadvantages, and especially to describe appropriate selection and usefulness of different spontaneous rodent models in testing of various new antidiabetic drugs for the treatment of type 2 diabetes.